Mewujudkan Desa Wisata Berbasis UMKM Melalui Festival Bazar di Kelurahan Jepara - Eni Indarwati; Moch. Nur Samsudin; Virginia Mandasari; Ayundha Evanthi; Susi Hardjati (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The Independent Learning Thematic Real Work Lecture or what is called (KKNT-MBKM) is one of the tri dharma of higher education whose function is as a means for community service. Community service in Jepara Village through this Real Work Lecture aims to take advantage of the potential of tourist villages in Jepara Village, Bubutan District, Surabaya. To optimize this potential, a tourism village development was held through the introduction of MSME products by holding a Culinary Bazaar Festival in the Jepara Village area. This study uses qualitative research methods with descriptive research type which aims to describe how the introduction of SMEs in Jepara Village through three stages, namely preparation of activities, implementation of activities, and reporting of activities. The results obtained from this study indicate that the introduction of MSME products sold at the culinary bazaar festival has increased sales. After this activity, it is hoped that local MSMEs in the Jepara region will have high competitiveness and have a wider (consumer) market share.